Effect of live weight on libido, sperm quality, testosterone and lute-inizing hormone in replacement stock of Ongole Grade bull - Affandhy, L.; Fitrayady, H.P.; Luthfi, M.; Widyaningrum, Y. (Journal of the Indonesian Tropical Animal Agriculture, 2018)
The objective of this study was to determine the effect of live weight (LW) on libido, sperm quality, testosterone, luteinizing hormone (LH) in Ongole grade (OG) bull. This study used 32 heads of OG bull with a completely randomized design that were divided to four different LW groups, i.e. group I was 170 to <210kg, group II was 210 to <250kg, group III was 250 to <290kg and group IV was 290 to 330kg. Parameters: observed were libido, testosterone hormone, LH, and semen quality. Data were analyzed by ANOVA. Libido of OG bull in group II and III higher than those in group IV. The testosterone hormone and LH showed that group II, III and IV were better than group I. The highest LH was in group IV, but low levels of testosterone were observed in these respective groups. Live sperm was the lowest in group I (21.25±13,20%) than II (66.00±11.17%), III (59.80±22.20%) and IV (75,67±9.46%). It can be concluded that the libido, sperm quality, testosterone, LH of OG bull in group II, III and IV were better than those in the group I, therefore standard LW of OG bulls had at least 250 kg.